2021
DOI: 10.1101/2021.12.04.471113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activating alternative transport modes in a multidrug resistance efflux pump to confer chemical susceptibility

Abstract: Small multidrug resistance (SMR) transporters perform coupled antiport of protons and toxic substrates, contributing to antibiotic resistance through efflux of these compounds from the bacterial cytoplasm. Extensive biophysical studies of the molecular transport mechanism of the E. coli SMR transporter EmrE indicate that it should also be capable of performing proton/drug symport or uniport, either of which will lead to drug susceptibility rather than drug resistance in vivo. Here we show that EmrE does indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…These results show some variation in specific substrate profile for each SMR homolog, as expected based on sequence variation in regions of the transporter known to be important for substrate binding and specificity. Although the results of the growth and metabolic assays characterizing the ability of SMR transporters to confer susceptibility or resistance to different compound in E. coli are not perfectly consistent, these orthogonal assays confirm that the functional promiscuity previously described for EmrE (34) does extend to at least three other SMR homologs across the same subfamily.…”
Section: Growth Assays and Dose-response Curves Confirm The Metabolic...mentioning
confidence: 54%
See 3 more Smart Citations
“…These results show some variation in specific substrate profile for each SMR homolog, as expected based on sequence variation in regions of the transporter known to be important for substrate binding and specificity. Although the results of the growth and metabolic assays characterizing the ability of SMR transporters to confer susceptibility or resistance to different compound in E. coli are not perfectly consistent, these orthogonal assays confirm that the functional promiscuity previously described for EmrE (34) does extend to at least three other SMR homologs across the same subfamily.…”
Section: Growth Assays and Dose-response Curves Confirm The Metabolic...mentioning
confidence: 54%
“…Many known SMR substrates are polyaromatic cations, and this commercially available assay is designed to avoid interference from the natural fluorescence of such compounds, enabling a single consistent assay format for characterization across several hundred potential substrates selected without bias towards common MDR efflux pump substrates. Our recent Biolog phenotypic microarray screen of E. coli revealed that EmrE confers resistance or susceptibility depending on the identity of the substrate, an unprecedented result (34). Here we repeat this screen on SAsmr, PAsmr, and FTsmr expressed in MG1655 Δ emrE E. coli cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, structural homology with SLC35/DMT transporters suggests that, contrary to the proposal that the SMRs are unusual in having not evolved fused, inverted repeat architecture ( 29 ), it is probable that the SMR fold has indeed been preserved through this evolutionary mechanism, albeit with a helical insertion and domain swap along the way. These recent advances in understanding the molecular architecture bolster ongoing efforts to develop antimicrobials that target SMR proteins, either by inhibiting transporter assembly in order to sensitize bacteria to transported compounds ( 78 , 137 , 138 ) or by hijacking the nominal exporters to import antimicrobial compounds instead ( 139 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%